(untitled) (Global Journal of Management and Business Research, 2019)
Bangladesh is a densely populated country of the world. More than 170 million people live in this country. Mobile banking is a very important and new phenomenon in Bangladesh. In recent years, mobile banking has got highest importance by the customers in the country as it provides immense scope for consumers for banking transactions at any time with the option to access bank#x2019;s facilities anywhere of the country. It is a subset of electronic banking, the use of which is increasing day by day in Bangladesh. Hence, this paper aims at indentifying the factors that influence the customer experience in mobile banking in Bangladesh. This study is based on a survey of 231 mobile banking customers of nine private commercial banks of Bangladesh. Literature review identified some factors related to mobile banking like convenient and responsive system, transaction speed and accuracy, reliability, transaction security in ATM booth and technological difficulty that affect customers#x2019; experience in mobile banking systems etc. Both descriptive and inferential statistics were used to analyze the data. Descriptive statistics were used to describe the present situation of the mobile banking systems in Bangladesh.